ASSOCIATION BETWEEN EXISTENCE SIBLING AND PRAGMATIC ABILITY AMONG PRESCHOOL CHILDREN: PATH ANALYSIS EVIDENCE FROM SURAKARTA - Nadya Susanti; Anggi Resina Putri (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: In each phase of development, children do not only grow physically, but also from a psychological to intellectual point of view. Children who don't get enough stimulation may show signs of developmental problems in their language and speech. The presence of siblings can affect the development of personality and the ability to communicate with children. Children who have existence siblings get more language and speech stimulation from their parents and siblings.Methods: This study used a cross sectional study design, which was conducted in Surakarta City. A sample of 200 people was selected using a random sampling technique. Data collection was performed using a questionnaire and analyzed by path analysis.Results: There was a direct relationship between children with siblings having a log odds of good pragmatic skill 4.97 units higher than children without siblings (b=4.97; 95% CI= 3.70 to 6.24; p= <0.001). Positive parenting styles had a log odds of experiencing good pragmatic skill of 3.42 units higher than children with negative parenting styles (b=3.42; 95% CI= 2.10 to 4.69; p= <0.001). Children who have existence siblings are indirectly related to pragmatic skill through parenting style. Children with existence siblings had the possibility of having good pragmatics skill by 1.73 units higher than children without siblings (b=1.73; 95% CI= 1.07 to 2.3; p= <0.001).Conclusion: Good pragmatic skill was directly influenced by the existence sibling and positive parenting style. Pragmatic abilities are indirectly related to existence sibling through positive parenting style.